Penerapan Mobilisasi Progresif terhadap Kejadian Dekubitus pada Pasien dengan Penurunan Kesadaran di HCU Anggrek 2 Rumah Sakit Dr. Moewardi - Lailatul Salsabela; Bagas Biyanzah Drajad Pamukhti; Isti Wulandari (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Pressure ulcers are a common complication in patients with impaired consciousness due to prolonged immobilization. This condition can increase morbidity and prolong the length of stay, thus requiring effective preventive interventions such as progressive mobilization. To determine the outcomes of implementing progressive mobilization on the incidence of pressure ulcers in patients with impaired consciousness at the Anggrek 2 High Care Unit (HCU) of Dr. Moewardi General Hospital. This study employed a case study design involving two participants with impaired consciousness. The intervention, consisting of progressive mobilization, was conducted over 3 days with monitoring of skin condition and pressure ulcer risk. Findings: Following the implementation of progressive mobilization, both participants showed improvement in skin condition and a reduction in the risk of pressure ulcers, as evidenced by the absence of progression to more severe wounds and an increase in skin integrity. The application of progressive mobilization is effective in preventing and reducing the risk of pressure ulcers in patients with impaired consciousness. This intervention can serve as a safe and planned nursing intervention in the intensive care unit.